Current concepts in the evaluation and management of preoperative anemia. Issue 3 (June 2021) - Neef, Vanessa; Choorapoikayil, Suma; Piekarski, Florian; Schlesinger, Tobias; Meybohm, Patrick; Zacharowski, Kai
Abstract : Purpose of review: In the past years, patient blood management (PBM) has evolved to improve patient's care and safety. Anemia is one of the most common medical diseases in the world and is an independent risk factor for morbidity and mortality. Iron deficiency is the main cause for anemia and constitutes a potentially preventable condition with a great impact on surgical outcome. However, preoperative anemia management is not yet established in most hospitals. Changing workflows and re-thinking is challenging. Numerous published studies confirmed the positive effect of preoperative anemia diagnosis and treatment recently. Recent findings: Iron supplementation in iron-deficient anemic (IDA) patients reduce the need for allogenic blood transfusion thereby improving perioperative outcome. Summary: Since the introduction of PBM programs, important movements towards early detection and therapy of preoperative anemia have been observed. However, preoperative anemia management is not implemented on a large scale as many healthcare professionals are not aware of the most recent findings in the field. Preoperative anemia management, particularly iron supplementation in IDA patients, has proven to be highly effective and has a tremendous effect on patient safety and outcome.